Study of Water Quality Index of Cilamaya Watershed Before and During The COVID-19 Pandemic - Nur Fitri; Wisnu Prayogo; M. Faisi Ikhwali; Rachmat Mulyana; Ahmad Zulfikar (Journal of Sustainable Infrastructure, 2022)
Due to the Covid-19 pandemic, the impact of the lockdown on the water quality of major rivers due to restrictions on activities within the country will have an effect. This research compared the Cimalaya Watershed water quality index values before and during the Covid-19 pandemic. River status was conducted using STORET and Pollution Index based on 2019 and 2020 river quality data. Calculations for each method use the same amount of data and parameters, including TSS DO, BOD, COD, TP, Fecal Coliform, and Total Coliform. The results showed a decrease in concentration for water quality parameters in 2020 or during the Covid-19 pandemic compared to 2019. The parameters that experienced a reduction included TSS, DO, BOD, and COD. But besides that, there has been an increase in water quality parameters in 2020, namely the parameters TP, Fecal Coliform, and Total Coliform. The average STORET and Pollution Index values in 2020 indicated that the river is getting moderately polluted than in 2019. This research can be a preliminary study, but using more parameters and methods will make the analysis more comprehensive.